What Drives International Students to Choose Australia as Their Tertiary Education Destination? A Synthesis of Empirical Evidence - Ha, Nguyen Thi Ngoc; Hoang, Cuong Huu; Knight, Elizabeth; Hurley, Peter (Journal of International Students, 2023)
This systematic literature review synthesizes empirical evidence to comprehensively examine factors driving international students’ choice of Australia as their preferred destination for tertiary education. Deductive analysis of findings from the 46 selected studies, framed within the push and pull framework, identified 27 factors that revealed Australia’s distinctive attractiveness to international students. The results of this review reaffirmed the strengths of Australia’s environmental images in the international tertiary education market, highlighting that it could be a double-edged sword. The review discusses Australia’s attractiveness, especially after the COVID-19 crisis and suggests strategies to make the international education sector more sustainable. This review provides implications for policy, practice, and future research that are of importance to work towards enhancing Australia’s intake of international education. Additionally, it serves as a valuable resource for those seeking guidance on effectively attracting international students in the post-pandemic era.